Does energy tax subsidy policy promote the development of the biomass energy industry? A case of densified biomass fuel industry in China. (November 2022) - Yang, He; Bai, Yang; Guo, Jiao; Zeng, Zhi; Mi, Feng
Abstract: Global energy crisis and climate change have caused widespread concern about the development of the biomass energy industry. China has committed to exploring feasible policies to promote the development of the biomass energy industry. To analyze the impact of China's energy tax subsidy policy (ETS) on the development of densified biomass fuel (DBF) industry, this study constructs a partial equilibrium model of the densified biomass fuel industry sector to quantitatively evaluate and optimize the effect of China's current ETS policy based on the compilation of input–output table for the biomass energy industry sector in China. The results indicate that 1) under the current policy scenario, the price of DBF in China decreased by 15.05%, the supply increased by 40.75%, and the demand increased by 18.62%, while the price of raw biomass (RB) decreased by 14.75%, the supply increased by 42.44%, and the demand increased by 29.41%, and the revenue of enterprises increased by 20.42%. However, compared to China's 13th Five-Year Plan national DBF development target, there is still a supply and demand gap of 16, 560, 549 tons. 2) under the optimized policy scenario premised on accomplishing the Chinese government's DBF development goals, the price of DBF in China decreased by 6.9%, supply increased by 128.5%, and demand increased by 44.5%, while the price of raw biomass decreased by 7.84%, supply increased by 133.34%, demand increased by 45.71%, and corporate earnings rose by 112.1% but required the government to pay extremely high tax benefits and financial subsidies for this, which is not feasible in actual economic operation. Therefore, to support the sustainable development of the DBF industry, relevant departments should not only set the mandatory total target but also pursue production quality and market construction.